# F s(x) = x – 7 and t(x) = 4x2 – x + 3, which expression is equivalent to (t x s)

QUESTION POSTED AT 01/06/2020 - 02:57 PM

QUESTION POSTED AT 01/06/2020 - 02:57 PM

Hello :

s(x) = x – 7 and t(x) = 4x² – x + 3

(t x s)(x)= (x-7)(4x²-x+3) = 4x^3-x²+3x-28x²+7x-21

(t x s)(x)= 4x^3 -29x²+10x -21

s(x) = x – 7 and t(x) = 4x² – x + 3

(t x s)(x)= (x-7)(4x²-x+3) = 4x^3-x²+3x-28x²+7x-21

(t x s)(x)= 4x^3 -29x²+10x -21

QUESTION POSTED AT 02/06/2020 - 01:57 AM

QUESTION POSTED AT 02/06/2020 - 01:56 AM

QUESTION POSTED AT 02/06/2020 - 01:47 AM

QUESTION POSTED AT 02/06/2020 - 01:43 AM

QUESTION POSTED AT 02/06/2020 - 01:43 AM

QUESTION POSTED AT 02/06/2020 - 01:42 AM

QUESTION POSTED AT 02/06/2020 - 01:40 AM

QUESTION POSTED AT 02/06/2020 - 01:37 AM

QUESTION POSTED AT 02/06/2020 - 01:36 AM

QUESTION POSTED AT 02/06/2020 - 01:35 AM

QUESTION POSTED AT 02/06/2020 - 01:34 AM

QUESTION POSTED AT 02/06/2020 - 01:33 AM

QUESTION POSTED AT 02/06/2020 - 01:32 AM

QUESTION POSTED AT 02/06/2020 - 01:31 AM

QUESTION POSTED AT 02/06/2020 - 01:30 AM

QUESTION POSTED AT 02/06/2020 - 01:30 AM

QUESTION POSTED AT 02/06/2020 - 01:29 AM

QUESTION POSTED AT 02/06/2020 - 01:29 AM

QUESTION POSTED AT 02/06/2020 - 01:29 AM

QUESTION POSTED AT 02/06/2020 - 01:28 AM

QUESTION POSTED AT 02/06/2020 - 01:25 AM

QUESTION POSTED AT 02/06/2020 - 01:24 AM

QUESTION POSTED AT 02/06/2020 - 01:23 AM

QUESTION POSTED AT 02/06/2020 - 01:22 AM

QUESTION POSTED AT 02/06/2020 - 01:21 AM

QUESTION POSTED AT 02/06/2020 - 01:21 AM

QUESTION POSTED AT 02/06/2020 - 01:20 AM